Aromas from Quebec. VI. Morella pensylvanica from the Magdalen Islands: a (-)-α-bisabolol-rich oil featuring a new bisabolane ether. Issue 5 (3rd September 2018) - St-Gelais, Alexis; Roger, Benoit; Alsarraf, Jérôme; Legault, Jean; Massé, Dany; Pichette, André
Abstract: Aerial parts of northern bayberry ( Morella pensylvanica (Mirbel) Kartesz) from the Magdalen Islands were submitted to steam distillation to evaluate both yield and composition of essential oil and hydrosol. It yielded 0.15% (m/m) of a pleasantly scented essential oil featuring a different composition than that reported in Connecticut. This oil appeared to be rich in (-)-α-bisabolol, β-caryophyllene, linalyl acetate, geraniol and γ-terpinene. It also contained a new α-bisabolol derivative that was identified as 2, 2, 6-trimethyl-6-(4-methylcyclohex-3-en-1-yl)tetrahydro-2 H -pyran, and named Magdalen ether. The hydrosol contained 160 mg/L of aromatic compounds among which α-bisabolol, linalool, α-terpineol and α-bisabolol oxide B, and a few minor phenolic compounds. The oil was tested for its cytotoxicity in vitro on WS-1 human fibroblasts and was shown to be four times less cytotoxic than the generally recognized as safe α-bisabolol, but did not show anti-inflammatory properties through inhibition of nitrous oxide production by murine macrophages.